From the Author as Word-Assembler to the Author as Word/Image/Sound/Interactivity/Algorhythm-Assembler: Literary Management in the (Post) Digital Era - Rodríguez Ruiz, Jaime Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Understanding literature as language, information and communication management opens relevant per- spectives with regards to the challenges posed by the contemporary media outbreak. This paper propos- es a journey through four moments, differentiated by the evolution of communication modes and their frantic acceleration in recent years. Literature as management of certain textual dynamics; literature as intermedial management; literature as expanded scenario of fiction -given the extent of digital culture practices-, and literature as post-digital exercise. In the end, this tour becomes a space to be traveled synchronously, a map that offers a conceptual cartography inviting an exploratory journey through the transformations of today ́s increasingly complex and rich cultural landscape.